1997
DOI: 10.1002/(sici)1099-0720(199710)11:5<415::aid-acp469>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the age of eyewitnesses on the accuracy and suggestibility of their testimony

Abstract: Previous studies have compared the performance of young adult eyewitnesses with that of children or elderly eyewitnesses, but few studies have allowed direct comparison of the performance of all three age groups. The accuracy and suggestibility of accounts of a video recording of a kidnapping were investigated using an experimental eyewitness paradigm. Subjects were drawn from three age groups: children (aged 7–9 years); young adults (aged 16–18 years) and elderly subjects (aged 60–85 years). Subjects' accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 31 publications
4
24
0
2
Order By: Relevance
“…This pattern of behavior is particularly worrisome, given the influence of eyewitness confidence on jury decision making. Further research is critical for determining the generality of our findings, since some studies have shown no age-related differences in the overall magnitude of the suggestibility effect, although no other study has been performed to examine how the tendency to make suggestibility errors varies with changes in confidence (e.g., Coxon & Valentine, 1997;Gabbert, Memon, & Allan, 2003; see Bartlett & Memon, in press, for a review). Finally, a favorable result emerged in the performance of the younger adults in the delay condition.…”
Section: Discussionmentioning
confidence: 87%
“…This pattern of behavior is particularly worrisome, given the influence of eyewitness confidence on jury decision making. Further research is critical for determining the generality of our findings, since some studies have shown no age-related differences in the overall magnitude of the suggestibility effect, although no other study has been performed to examine how the tendency to make suggestibility errors varies with changes in confidence (e.g., Coxon & Valentine, 1997;Gabbert, Memon, & Allan, 2003; see Bartlett & Memon, in press, for a review). Finally, a favorable result emerged in the performance of the younger adults in the delay condition.…”
Section: Discussionmentioning
confidence: 87%
“…Our review of the literature yielded three studies in which older adults were more suggestible than younger adults (Cohen & Faulkner, 1989;Loftus, Levidow, & Duensing, 1992;Mitchell, Johnson, & Mather, 2002). A fourth study found no age differences in suggestibility (Coxon & Valentine, 1997), and a fifth found younger adults to be more suggestible in some circumstances (Marche, Jordan, & Owre, 2002). Suggestibility in the eyewitness and other paradigms does not necessarily imply suggestibility in the fiction paradigm.…”
Section: Memory In Healthy Older Adultsmentioning
confidence: 99%
“…These age diVerences might reasonably be expected to extend to eyewitness identi cation. Qualifying this expectation, however, are mixed results from the few studies testing for age diVerences in misleading information eVects in the eyewitness paradigm (Cohen & Faulkner, 1989;Weingard, Toland, & Loftus, 1994; but see Coxon & Valentine, 1997). A possible reason for the inconsistent ndings with respect to age diVerences might be variations in the context in which the misinformation is presented.…”
Section: Evects Of Post-event Informationmentioning
confidence: 99%